2019
DOI: 10.1007/s10327-019-00863-9
|View full text |Cite
|
Sign up to set email alerts
|

A class III peroxidase PRX34 is a component of disease resistance in Arabidopsis

Abstract: PRX34 mediates the oxidative burst in Arabidopsis. Here we characterized two additional Arabidopsis prx34 null mutants (prx34-2, prx34-3), besides the well-studied prx34-1. Due to a decrease in corresponding peroxidase, the activity that generates reactive oxygen species (ROS) was significantly lower in cell wall extracts of prx34-2 and prx34-3 plants. Consistently, the prx34-2 and prx34-3 exhibited reduced accumulation both of ROS and callose in Flg22-elicitor-treated leaves, leading to enhanced susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A characterization study also demonstrated that the Arabidopsis mutant prx34 can reduce ROS and callose accumulation after Flg22-elicitor treatment. These results corroborate other findings, showing that the PRX34 enzyme could be an important component for plant disease resistance [83].…”
Section: Pr-9 Family: Peroxidasessupporting
confidence: 92%
“…A characterization study also demonstrated that the Arabidopsis mutant prx34 can reduce ROS and callose accumulation after Flg22-elicitor treatment. These results corroborate other findings, showing that the PRX34 enzyme could be an important component for plant disease resistance [83].…”
Section: Pr-9 Family: Peroxidasessupporting
confidence: 92%
“…The oxidative burst induced by pathogenderived signals is essential to defense mechanisms throughout the plant (Fobert and Després, 2005). Apoplastic ROS are generated from plasma membrane-localized NADPH oxidases and cell wall-localized peroxidases (Zhao et al, 2019). ROS are known as antimicrobial molecules involved in cell wall reinforcement and callose deposition.…”
Section: Introductionmentioning
confidence: 99%
“…GLU enhances the tolerant of rough lemon rootstock against foot rot (Sandhu et al, 2019), improves the inhibition of rice against Rhizoctonia solani (Kumar et al, 2018), reduces the rice sheath blight (Kaur et al, 2021), and confers tea tree resistance against blister blight disease (Singh et al, 2018). POD is involved in the resistance response of coffee varieties to Colletotrichum kahawae (Diniz et al, 2019), potato to P. infestans , Arabidopsis thaliana to Botrytis cinerea, Colletotrichum higginsianum, and Pectobacterium carotovorum (Zhao et al, 2019), Citrus sinensis to citrus bacterial canker (Li et al, 2020). CAT contributes maize to resistance against maize chlorotic mottle virus infection (Jiao et al, 2021), Nicotiana tabacum against Chilli veinal mottle virus infection (Yang T. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%